UPAYA PEMERINTAH KABUPATEN INDRAGIRI HULU DALAM PENGENTASAN ANAK PUTUS SEKOLAH (STUDI KASUS SEKOLAH DASAR DI KECAMATAN BATANG CENAKU TAHUN 2011-2012) - Rio Kusbowo; M.Y.Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The problems of school dropouts  is  like dynamite for Indonesian that never be ended because the number of school dropout rates increases each year, as happened in Indragiri Hulu, especially in BatangCenaku. The numbers of school dropouts  in elementary  level amounted to 66 students from 4856 students in 2011 while  in 2012  the numbers of schools  dropouts  increased to 188 students from 4951  students.A negative impact for  the Indragiri Hulu if the problem can not be solved by the government of Indragiri Hulu. So the researcher  formulates what factors are the causes of school dropouts at the elementary level in BatangCenaku? How are the efforts of local government of educational sector in the reduction of school dropouts in BatangCenaku?This  is a qualitative research. The location of this  study  is at the office of District Education of  Indragiri Hulu, in Batang Cenaku. In  collecting  the data the researcher  used purposive sampling technique.  Purposive sampling is  a  technique that usedparticular consideration  in collecting the data sample, for example, the person considered  as  most knowledgeable about what  to  expect, so it will be easier for researcher to explore objects and social situation investigated. To get the data,  the  researcher  used  the following methods: observation, interviews, and documentation. To describe the issues discussed,  analyzing the data  is needed to do.According to the  finding  research the causes of school dropouts are  the economy, family, school, peers,  and  academic ability. The efforts of the Government of Indragiri Hulu  appropriate    toauthority possessed by the local government issued a policy of reduction of school dropouts in the form of movement compulsory  education of  villages  based  including updating data dropouts or no schooling  children, socialization to the people, Assistance Fund, Optimizing Scholarship Education for  poor  people,  and Education Pack Assistance Program.Keywords: Authority, Dropouts, Education